Effect of strip tillage widths on soil moisture, soil temperature and soil structure in northeast China - Wang, Chenglin; Ai, Sizhe; Chen, Qiang; Li, Jianye; Ding, Jiahua; Yang, Fan (Frontiers in Environmental Science, 2024)
Strip tillage (ST) is an effective tillage technique, which included the strip seedbed tilled area (ST-IR) and the straw-covered area between the seedbeds (ST-BR). However, soil hydrothermal conditions and soil disturbance varies with strip tillage widths, which might affect crop growth and yields. Therefore, this study explored the effect of strip tillage width on the soil hydrothermal conditions and soil structure of ST-IR and ST-BR, to determine the optimal strip tillage width. A field experiment with three replicates was conducted to analyze soil moisture and soil temperature variation and to clarify the difference of soil structure in the IR and BR. Three strip tillage widths, 20 cm (ST20), 30 cm (ST30), and 40 cm (ST40), were examined in this study. Soil temperature in both the ST-IR and ST-BR increased as the strip tillage width increased, and the average soil temperature of ST30-IR and ST40-IR in the seedling stage was 2.11 °C and 2.62 °C higher than that of ST20-IR, respectively. Moreover, the daily soil temperature range in both the IR and BR was greater for ST40 than for ST20 and ST30 in the seedling stage; soil temperature differences in other crop growth stages were small. No significant difference in soil temperature was observed between ST30-IR and ST40-IR. Conversely, soil moisture was greater in ST20-IR and ST30-IR than in ST40-IR; soil moisture was also greater in ST30-BR and ST40-BR than in ST20-BR during the monitoring period. Soil moisture in ST40-IR and ST20-BR increased and decreased more rapidly during rainfall events than in the other treatments. Moreover, soil temperature was higher in the ST-IR than in the ST-BR for all three strip tillage widths, and the opposite results were observed for soil moisture. In addition, strip tillage widths had no significant differences on soil structure. In conclusion, a 30 cm strip tillage width had higher soil temperature and remained more soil moisture than other strip tillage widths, so this strip tillage width is thus recommended for use by farmers in Northeast China.